2022
DOI: 10.3389/fonc.2022.1011230
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepatocyte nuclear factor 4α (HNF4α) in tumorigenesis

Abstract: Hepatocyte Nuclear Factor 4 Alpha (HNF4α) is a master transcription factor mainly expressed in the liver, kidney, intestine and endocrine pancreas. It regulates multiple target genes involved in embryonic development and metabolism. HNF4α-related diseases include non-alcoholic fatty liver disease (NAFLD), obesity, hypertension, hyperlipidemia, metabolic syndrome and diabetes mellitus. Recently, HNF4α has been emerging as a key player in a variety of cancers. In this review, we summarized the role and mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that HNF4α could behave as either a tumor suppressor or an oncogene largely depending on the tumor type and organ[10, 18, 19]. Thus, we next investigated the function of HNF4α in CRC by stable transfection of HNF4α into SW480 and SW620 colon cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that HNF4α could behave as either a tumor suppressor or an oncogene largely depending on the tumor type and organ[10, 18, 19]. Thus, we next investigated the function of HNF4α in CRC by stable transfection of HNF4α into SW480 and SW620 colon cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that the loss of nhr-14 gene in c. elegans resulted in the dysregulation of DNA damage-induced response [14], which usually leads to cancer development [15][16][17][18]. Thus, we examined HNF4α expression levels in different cancers and matched paired normal tissues.…”
Section: Hnf4 α Promotes Colorectal Carcinogenesismentioning
confidence: 99%
“…Some visualized figures are generated in real time to allow investigation of the cancer-type specificity and potential targets of enriched TFs (Figure 2E ). For instance, HNF4A, a well-established gastrointestinal-specific transcription factor ( 54 ), ranked as the second most enriched TF in colorectal cancer-specific CREs (Figure 2D ). HNF4A exhibited the highest expression levels in both colorectal cancer tissues and cell lines, regulated many target genes and was essential for the viability of the majority of colorectal cancer cells in the unbiased high-throughput CRISPR screening (Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…The transcription of NTCP and cytochromes P450 (CYPs) is reported to be regulated by hepatocyte nuclear factors (HNFs) [ 34 , 35 , 36 ]. Particularly, HNF1α and HNF4α are highly expressed in CRC tumors, the former is linked with tumor malignancy of CRC cells and the latter is considered as a critical risk factor for CRC [ 37 , 38 , 39 ]. HNF4α is known to be a direct trans-activator of NTCP and CYPs [ 34 , 35 , 40 ].…”
Section: Discussionmentioning
confidence: 99%